Experimental investigation on system performance using palm oil as hydraulic fluid - Nik, W.B. Wan; Maleque, M.A.; Ani, F.N.; Masjuki, H.H. (EMERALD GROUP PUBLISHING LIMITED, 2007)
Purpose - The aim of this paper is to investigate hydraulic system performance using vegetable-based palm oil as hydraulic fluid.